Perception of Kwara State undergraduates on the contributions of online tools towards improvement of reading habit - Sulaiman, Kabir Alabi; Akanbi, M. A. (Record and Library Journal, 2020)
Background of the study: The study aimed at examining perceptions of undergraduates on the contributions of online tools towards improvement of reading habit in Kwara state in universities. The study identified six (6) research questions. The research population was limited to undergraduates at the University of Ilorin, Kwara State University, Malate and Al-Hikmah University.Purpose: The study adopted descriptive survey design with questionnaire to collect data. The simple random sampling technique was adopted. The researcher used Educational and Psychological Measurement Israel model (2003) sample table to arrive at the actual sample size for this study. Therefore, the sample size for this study at level of Â± 5% level of significance for population of 53, 130 students was 397. With total population of 76% for University of Ilorin, 18% for Kwara State University Malate and 6% for Al-Hikmah University, Ilorin.Method: Data collected from the field were analyzed using descriptive method of analysis.Findings: The findings of the study revealed that blog, twitters, E-mail, websites, YouTube, Facebook is the most available online tools that improve undergraduates reading habit. The study also revealed that undergraduates using online tools for social purpose than others.Conclusion: The study concluded that undergraduates have good perception using online tools for their reading. The study also established that undergraduates using online tools for social, political, recreation and religion benefits. It is also established that distraction, fallout from technologies, financial constraints and poor power supply are the major setbacks to the use of online tools for reading.